Improvement of Mechanical Behavior of FSW Dissimilar Aluminum Alloys by Postweld Heat Treatments. (16th September 2022) - Prabhu, S.; Sri, M. Naga Swapna; Anusha, P.; Saravanan, G.; Kannan, K.; Manickam, Selvaraj
Abstract : AA6262 and AA5456 alloys are welded through friction stir weld (FSW) with process parameters of tool speed of 1200 rpm, welding speed of 25 mm/min, and tool angle of 3 degree. A cylindrical shape HSS-13 tool is used to perform the welding process To improve mechanical properties of tensile strength (TS), yield strength (YS), elongation%, hardness, and wear behavior, postweld heat treatment was conducted on the FSW sample at different temperatures from 300°C to 500°C. The influence of heat treatment (HT) changes the material characteristics. It is observed that the maximum TS (209 MPa) and YS (178 MPa) are identified when maintaining temperature 350°C on the FSW sample. The reduction in elongation of as-welded joints is entirely improved by HT, and the elongation percentage is almost increased to 5% when increasing temperature on the heat treatment process, and hardness test results exhibited that the increased hardness value (120Hv) is found at HT-300°C nugget zone distance of 0 to 5 mm range.